An Approach to Build P2P Web Extensions - González, Rodolfo (2020)
Web extensions are currently the most frequently used mechanism for end-users to externally adapt and enrich the web. While most functionality offered by extensions runs on the browser, extensions that offer collaboration, complex computation, or massive storage rely on a centralized server. Relying on a server increases the cost of building, deploying, and maintaining web extensions (even small ones). This paper presents a novel P2P approach to build web extensions. It removes the need for a centralized server while hiding behind a framework the complexity of building P2P extensions. It uses a middleware to manage the resources offered by the browser so multiple P2P extensions can coexist, without degrading the browser's performance. This paper discusses the main challenges of building P2P web extensions, presents the approach, and shows its potential with a proof of concept.